Gimme kudos. (China : Centre of International Cultural Exchange, China for.)
On a rainy evenig a peasant worker, Yang Hongqi, happens uppon and saves a university student, Ouyang Hua, from being raped. In order to make his father's dying wish come true, he pursues a newspaper journalist, hoping that the journalist will commend his good deed in print.
Keywords: Cultural Center of China